Increased Equality of Opportunity Thorough International Tourism - Scott A. Hipsher (Journal of International Conference Proceedings (JICP), 2018)
There is debate over the impact of international tourism on creating quality jobs and reducing poverty in developing economies. This paper explores the perceptions of entry level and non-managerial workers of the impact of international tourism on both their own lives and the country as a whole. A matched-pairs analysis was used to compare the views of workers in Thai-owned versus foreign-owned companies. Overall the workers perceptions were positive on the impact of tourism on their own lives and the country as a whole, while there was no significant difference between the workers’ attitudes in the two categories attitudes towards the impact on their own lives although workers in foreign-owned firms had significantly more positive attitudes towards the impact on the country as a whole than workers in Thai-owned companies. Keywords: international tourism, Thailand, workers perceptions, foreign-owned firms